KONTRIBUSI ECPAT (END CHILD PROSTITUTION, CHILD PORNOGRAPHY AND TRAFFICKING) TERHADAP AKTIFITAS SEX TOURISM DI BRAZIL TAHUN (2012-2014) - Amanda Riri Rizky; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The research describes the role of ECPAT through ethics commitees in tackling the problems of Sex Tourism in Brazil. Authors would like to clarify the role taken by ECPAT on issues that concern about the world tourism. The aim is to overcome the problems of exploitation in Brazilian children get in the tourism industry due to several factors cause children into the sex tourism industry.This study uses the theory of the role of international organizations as a tool used to analyze the role and responsbility of international organizations and the use of perspective Liberalism. The data is taken from books, journals and websites.This study will explain how ECPAT took its role as an international organizations in tackling the problem of child exploitation in the tourism industry in Brazil with running multiple programs of cooperation with local NGOs that concern about the problem of sexual exploitation of children in tourism.Keyword: ECPAT, Child Trafficking, Child Sex Tourism, Role, Exploitation Sexual